Demand for higher education programs: the impact of the Bologna process - Cardoso, Ana Rute (2007)
The Bologna process aims at creating a European Higher Education Area where inter-country mobility of students and staff, as well as workers holding a degree, is facilitated. While several aspects of the process deserve wide public support, the reduction of the length of the first cycle of studies to three years, in several continental European countries where it used to last for four or five years, is less consensual. The paper checks the extent of public confidence in the restructuring of higher education currently underway, by looking at its implications on the demand for academic programs in Portugal. Precise quantification of the demand for each academic program is facilitated by the rules of access to higher education, in a nation-wide competition, where candidates must list up to six preferences of institution and program. We use regression analysis applied to count data, estimating negative binomial models. Results indicate that the programs that restructured to follow the Bologna principles were subject to higher demand than comparable programs that did not restructure, as if Bologna were understood as a quality stamp. This positive impact was reinforced if the institution was a leader, i.e. the single one in the country that restructured that program. Still an additional increase in demand was experienced by large programs that restructured to offer an integrated master degree, thus conforming to Bologna principles while not reducing the program duration.program is facilitated by the rules of access to higher education, in a nation-wide competition, where candidates must list up to six preferences of institution and program. We use regression analysis applied to count data, estimating negative binomial models. Results indicate that the programs that restructured to follow the Bologna principles were subject to higher demand than comparable programs that did not restructure, as if Bologna were understood as a quality stamp. This positive impact was reinforced if the institution was a leader, i.e. the single one in the country that restructured that program. Still an additional increase in demand was experienced by large programs that restructured to offer an integrated master degree, thus conforming to Bologna principles while not reducing the program duration.